2004
DOI: 10.2337/diabetes.53.1.228
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Search for Type 2 Diabetes/Impaired Glucose Homeostasis Susceptibility Genes in the Chinese

Abstract: This genome-wide search for susceptibility genes to type 2 diabetes/impaired glucose homeostasis (IGH) was performed on a relatively homogenous Chinese sample with a total number of 257 pedigrees and 385 affected sibpairs. Two regions showed significant linkage to type 2 diabetes/IGH in the Chinese. T ype 2 diabetes is a complex disease that develops in individuals with genetic susceptibility to impaired insulin secretion, as well as to impaired insulin sensitivity, in the presence of appropriate environmental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
93
0
4

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 151 publications
(100 citation statements)
references
References 36 publications
3
93
0
4
Order By: Relevance
“…The involvement of PC-1 in insulin-resistant states is further supported by recent studies revealing evidence for linkage between the chromosomal region 6q22-q23 of the gene encoding PC-1 (ENPP1) and insulin resistance [9], obesity [10,11] and type 2 diabetes [12][13][14][15]. Furthermore, the minor Q allele of a K121Q variant (rs1044498) of ENPP1 has been shown to influence PC-1 protein function by inhibiting insulin receptor function and insulin signalling more effectively than the major K allele [16,17].…”
mentioning
confidence: 74%
“…The involvement of PC-1 in insulin-resistant states is further supported by recent studies revealing evidence for linkage between the chromosomal region 6q22-q23 of the gene encoding PC-1 (ENPP1) and insulin resistance [9], obesity [10,11] and type 2 diabetes [12][13][14][15]. Furthermore, the minor Q allele of a K121Q variant (rs1044498) of ENPP1 has been shown to influence PC-1 protein function by inhibiting insulin receptor function and insulin signalling more effectively than the major K allele [16,17].…”
mentioning
confidence: 74%
“…[1][2] Genetic and genome-wide association studies in recent decades have identified many different candidate genes that are related to susceptibility in various populations. [3][4][5] The ectonucleotide pyrophosphatase/phosphodiesterase 1 (ENPP1) gene, also known as plasma cell membrane glycoprotein 1, localizes on chromosome 6q23.2, a region that has been reported to be being linked to obesity, 6 serum insulin levels 7 and T2D 8,9 in different populations. ENPP1 encodes for a type II transmembrane glycoprotein that inhibits insulin receptor (IR) tyrosine kinase activity 10 and subsequent insulin signaling by a likely direct interaction with the a-subunit of IR.…”
Section: Introductionmentioning
confidence: 99%
“…20 This region is approximately 160 to 180 cM from p-telomere and corresponds to a region of chromosome 1 that has been linked to T2DM in several other populations, including Pima Indians, 21 Utah Mormons, 22 British whites, 23 French whites, 24 and Chinese. 25 Familial partial lipodystrophy is a condition associated with severe insulin resistance, diabetes, dyslipidemia, and atherosclerosis, 26 making LMNA an excellent positional candidate gene for metabolic syndrome, T2DM, and related traits. LMNA, located on chromosome 1q21.2, encodes a nuclear envelope protein that exists as a heterodimer of lamin A and lamin C and is expressed in several cell types including liver, fat, muscle, and pancreas.…”
mentioning
confidence: 99%